2015
DOI: 10.1039/c4np00104d
|View full text |Cite
|
Sign up to set email alerts
|

Biological targets and mechanisms of action of natural products from marine cyanobacteria

Abstract: Marine cyanobacteria are an ancient group of organisms and prolific producers of bioactive secondary metabolites. These compounds are presumably optimized by evolution over billions of years to exert high affinity for their intended biological target in the ecologically relevant organism but likely also possess activity in different biological contexts such as human cells. Screening of marine cyanobacterial extracts for bioactive natural products has largely focused on cancer cell viability; however, diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 191 publications
(501 reference statements)
0
115
0
Order By: Relevance
“…Over the last two decades, the range of availablem ethods used to identify relevant biological targets and mode of action of small-molecule NPs has changed dramatically.T he discussion is out of the scope of this paper,b ut these methods were reviewed for marine NPs recently. [144,145] Table 2. Strategies to identify bioactive compoundsf rom natural extracts.…”
Section: Role Of Nps In Drug Discoverymentioning
confidence: 99%
“…Over the last two decades, the range of availablem ethods used to identify relevant biological targets and mode of action of small-molecule NPs has changed dramatically.T he discussion is out of the scope of this paper,b ut these methods were reviewed for marine NPs recently. [144,145] Table 2. Strategies to identify bioactive compoundsf rom natural extracts.…”
Section: Role Of Nps In Drug Discoverymentioning
confidence: 99%
“…39,226 Even after correlating metabolites with biological activity, determining the mode of action for active compounds can be difficult and expensive. 227-230 One approach has been developed that uses the antibiotic spectrum of activities across different organisms, mode of action profiles (BioMAP), to group similar antibiotics. 231 This method was effectively able to cluster antibiotics of the same compound class and led to the identification of a novel naphthoquinone antibiotic, arromycin.…”
Section: Investigations Of Secondary Metabolite Bioactivitymentioning
confidence: 99%
“…The chemical diversity of secondary metabolites reported to date has shown that marine cyanobacteria are an excellent resource for the discovery of new compounds . Furthermore, marine cyanobacteria have been shown to be a source for secondary metabolites with interesting bioactivities and mechanisms of action . In our continuing search for new metabolites from marine cyanobacteria, we have isolated a macrolide xylopyranoside trivially named cocosolide ( 1 ) from the lipophilic extracts of the soft, golden cyanobacterium preliminarily identified as Symploca sp.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Furthermore, marine cyanobacteria have been shown to be as ource for secondary metabolites with interesting bioactivities and mecha-nisms of action. [2,3] In our continuing search for new metabolites from marinec yanobacteria, we have isolated am acrolide xylopyranosidet rivially namedc ocosolide (1)f rom the lipophilic extractso ft he soft, golden cyanobacterium preliminarily identified as Symploca sp.c ollected from Cocos Lagoona nd Ta nguisson reef flat, Guam. Cocosolide is as ymmetrical dimer, which structurally resembles the sponge metabolites clavosolides A-D isolated from aP hilippine collection of the sponge Myriastrac lavosa [4,5] andc yanolide Ao btained from aP apua New Guinea collectiono fLyngbya bouillonii (Figure 1).…”
Section: Introductionmentioning
confidence: 99%